Reproductive Biology of Geodia Species (Porifera, Tetractinellida) From Boreo-Arctic North-Atlantic Deep-Sea Sponge Grounds - Koutsouveli, Vasiliki; Cárdenas, Paco; Conejero, Maria; Rapp, Hans Tore; Riesgo, Ana (Frontiers in Marine Science, 2020)
Boreo-arctic sponge grounds are essential deep-sea structural habitats that provide important services for the ecosystem. These large sponge aggregations are dominated by demosponges of the genus Geodia (order Tetractinellida, family Geodiidae). However, little is known about the basic biological features of these species, such as their life cycle and dispersal capabilities. Here, we surveyed five deep-sea species of Geodia from the North-Atlantic Ocean and studied their reproductive cycle and strategy using light and electron microscopy. The five species were oviparous and gonochoristic. Synchronous development was observed at individual and population level in most of the species. Oocytes had diameters ranging from 8 μm in previtellogenic stage to 103 μm in vitellogenic stage. At vitellogenic stages, oocytes had high abundance of lipid yolk entirely acquired by autosynthesis, with no participation of nurse cells. Intense vertical transmission of bacterial symbionts to the oocytes by phagocytosis through pseudopodia was observed, especially in late stages of oogenesis. The density of oocytes within the sponge tissue was on average 10 oocytes/ mm2 across all species, higher than that of most temperate and tropical oviparous species studied elsewhere. Spermatic cysts were widespread over the tissue during early stages, or fused in larger cysts, around the canals in later stages, and occupying between 1.5 and 12% of the tissue in males. The reproductive season spanned similar periods for all Geodia spp.: from late spring to early autumn. During the reproductive peak of each species, between 60 - 90% of the population was engaged in reproduction for most species, although the engagement was considerably lower for G. barretti (<20%) in some areas. Remarkably, no reproductive activity was detected in Korsfjord, either in spring or in early autumn for this species. Given the present hazards that threaten the boreo-arctic tetractinellid sponge grounds, it becomes crucial to understand the processes behind the maintenance and regeneration of populations of keystone deep-sea species in order to predict the magnitude of human impacts and estimate their ability to recover. The information provided in this study will be useful for developing adequate conservation strategies for these vulnerable deep-sea habitats.